Pan is Our Culture: It Must be Cherished not Jeered At - Unknown (Daily Express)
In this letter to the editor, the author comments on some observations of crowd behaviour at the 1981 Panorama Competition. It also focus on the issues of competition and the effects on Trinidad and Tobago's culture and society.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Administration -- Trinidad and Tobago